2020
DOI: 10.1080/14728222.2020.1712593
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Rho-associated coiled-coil forming protein kinase (ROCK) in cardiovascular fibrosis and stiffening

Abstract: Introduction: Pathological cardiac fibrosis, through excessive extracellular matrix protein deposition from fibroblasts and pro-fibrotic immune responses and vascular stiffening is associated with most forms of cardiovascular disease. Pathological cardiac fibrosis and stiffening can lead to heart failure and arrythmias and vascular stiffening may lead to hypertension. ROCK, a serine/ threonine kinase downstream of the Rho-family of GTPases, may regulate many pro-fibrotic and pro-stiffening signaling pathways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 133 publications
(183 reference statements)
1
38
0
Order By: Relevance
“…The authors found that diffuse fibrosis and myocardial hypertrophy recovered to more normal levels during the first 2 months after aortic valve replacement, whereas focal fibrosis was comparatively permanent (Treibel et al, 2018). All of these myocardial damagerelated pathologic processes associated with reverse myocardial remodeling are promoted by ROCK activation (Shimizu and Liao, 2016;Dai et al, 2018;Yu et al, 2020). Our present findings of significant reverse remodeling 3 months after initiation of CRT in HFrEF are consistent with the role of ROCK activation in PBMCs as a marker of myocardial remodeling.…”
Section: Discussionsupporting
confidence: 88%
“…The authors found that diffuse fibrosis and myocardial hypertrophy recovered to more normal levels during the first 2 months after aortic valve replacement, whereas focal fibrosis was comparatively permanent (Treibel et al, 2018). All of these myocardial damagerelated pathologic processes associated with reverse myocardial remodeling are promoted by ROCK activation (Shimizu and Liao, 2016;Dai et al, 2018;Yu et al, 2020). Our present findings of significant reverse remodeling 3 months after initiation of CRT in HFrEF are consistent with the role of ROCK activation in PBMCs as a marker of myocardial remodeling.…”
Section: Discussionsupporting
confidence: 88%
“…These enzymes belong to the AGC family of serine/threonine protein kinases and exist in two isoforms: ROCK1 (also named ROKβ or p160 ROCK ), encoded by gene ROCK1 on locus 18q11.1 and first identified in human platelet extracts [ 20 ] and ROCK2 (also named ROKα or Rho-kinase) encoded by the gene ROCK2 on locus 2p25.1 and isolated from rat brain extracts [ 21 ]. In mammals, both ROCK isoforms are ubiquitous but ROCK1 predominates in the kidney, spleen, liver, and ROCK2 in the brain and the heart [ 22 , 23 ]. This distribution suggests different functions, as described below [ 24 ].…”
Section: Overview On Rock Structure and Functionsmentioning
confidence: 99%
“…Both isoforms of ROCK possess a similar tridimensional structure composed of three main regions: an N-terminal kinase domain, a Coiled-coil region containing the Rho-binding domain (RBD) and a C-terminal Pleckstrin homology domain (PHD), with an internal cysteine-rich zinc-finger domain [ 25 ]. The homology between ROCK1 and ROCK2 is equivalent to 65% along the entire protein but reaches over 90% in the kinase domain and they are almost identical in the ATP-binding site [ 23 , 24 , 25 ]. The kinase domain of ROCK is generally thought to be active, as indicated after cleavage by caspase-3 (for ROCK1) or granzyme B (for ROCK2), despite the slight catalytic activity of the enzyme.…”
Section: Overview On Rock Structure and Functionsmentioning
confidence: 99%
“…Mice were treated with 2% DSS (in total 3 cycles) to induce chronic inflammation and, in the last cycle, were intraperitoneally injected with vehicle or ROCK1 inhibitor (15 mg/kg/day). 30 Nine weeks later, the chronic colitis was established. All surviving mice were sacrificed for subsequent analysis.…”
Section: Dss-induced Chronic Colitis Murine Model Treated With Rock1 Inhibitormentioning
confidence: 99%
“…When RhoA-GTP activates ROCK1, various proteins are phosphorylated, such as myosin light chains, leading to decreased dissociated globular actin, actin gathering and the occurrence of stress fibres. 21,22 ROCK1 is regarded as a potential candidate for antifibrotic therapy. 22 A small molecule ROCK inhibitor showed antifibrotic effects in a chronic intestinal inflammation-induced fibrosis model.…”
Section: Introductionmentioning
confidence: 99%